La richesse des aristocraties de Bétique et de Tarraconaise - autor, Sin (Gerión. Revista de Historia Antigua, 2005)
From the archaeological and litterary sources (notably the amphoras’ epigraphy), we try to present the chronological and spaceship tnethods of the economic expansión of Baetica and Tarraconensis (end of Ist.c ; B.C- IInd c. A. C), and to connect them with others criterions of integration of the provincial world as municipalization and apparence of an equestrian and senatorial elite. Then, we try to make an assessment of our knowledges about the composition of the means of an elite more and more influential in the political sphere. The implication of these families in the more dynamic sectors of the provincial economy emerges widely enough for Baetica, but leave more difficult to observe in Tarraconensis.